A Wii virtual activity severe thumb metacarpal injury - Galanopoulos, Ilias (BMJ Case Rep, 2012)
In this paper we present a case of a severe thumb bone injury sustained during simulated sporting activity using a Wii games console. Although several types of injury related to this form of physical activity have been encountered during the last few years with increasing frequency, this particular basal thumb fracture has not been reported in the literature yet. This was a complex Rolando type of fracture similar to those obtained doing the actual activity mimicked by the game. Ensuring a safe environment and adequate preparation before undertaking sport is key to prevent injury and the same principles are needed when undertaking virtual sport.